Europäische Wissenschaftskulturen und politische Ordnungen in der Moderne (1890-1970) - Hübinger, Gangolf (Schriften des Historischen Kollegs, 2014)
At the beginning of the 20th century, two revolutionary processes intersected in European industrialized societies. The sciences became a central force for interpreting the world, and the democratization of modern life became a key determinant of the political and cultural order. These processes turned Europe into a laboratory for very different interconnections between scientific self-observation and ideas about polity.